On the Development of a Mercury-free Ternary Aluminium Anode for Cathodic Protection - RAVINDRAN, K.; PILLAI, A. G. GOPALAKRISHNA (Fishery Technology, 2017)
The development of a new mercury-free ternary aluminium anode (CIFTAL) forcathodic protection of marine structures is described; The new anode demonstrated a current efficiency of 83.5 % to 85.4 % in a current density range of 5.6 to 166.7 mA dm - 2 • The current efficiency remained practically stable at 1.4 mAcm - 2 over a test period of 300 days. The service trials of the anode on steel trawlers and aluminium (Indal M 57 S) sheathed wooden boats have shown satisfactory performance in terms of unifonn dissolution, current efficiency and driving voltage. In the wake of legislations restricting the use of anodes containing mercury in an endeavour to control the mercury pollution of the near shore aquatic environment, the new anode (CIFTAL) with its stable current output and high current efficiency merits significance in marine cathodic protection.